THE SHIFTING ROLES OF TEACHERS AND STUDENTS: AN EFFECTIVE INTERACTION MODEL IN A CHATGPT-ENRICHED LEARNING ENVIRONMENT - Ali, Muhammad Makhrus; Zarfi, Syarifatul Hayati; Romdhane, Hana Ben; Wilson, Liam (Al-Hijr: Journal of Adulearn World, 2025)
The integration of artificial intelligence (AI) tools like ChatGPT into education is reshaping traditional roles of teachers and students. Traditionally, teachers have been the primary knowledge providers, while students acted as passive receivers of information. However, the advent of AI-powered tools, such as ChatGPT, challenges this dynamic by allowing for more interactive, personalized, and collaborative learning experiences. This study explores the shifting roles of teachers and students in a ChatGPT-enriched learning environment, focusing on the changes in classroom interaction and the impact on student engagement and teacher facilitation. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews, as well as classroom observations, to assess these changes. The results indicate that 75% of students reported increased engagement and autonomy in their learning, while 82% of teachers felt more effective in facilitating discussions and providing real-time feedback. The study concludes that ChatGPT enhances the teacher-student interaction by fostering a collaborative, student-centered learning environment where both parties contribute to knowledge construction. The findings suggest that the successful integration of AI into classrooms requires a shift toward more dynamic, interactive teaching methods and highlight the potential of ChatGPT in transforming educational practices.